الإطر القانونية والإجرائية للتحكيم في النزاعات الرياضية في القانون الإماراتي دراسة تحليلية مقارنه مع القانون المصري والفرنسي: Analysis of the legal and procedural framework for arbitration in sports disputes in UAE law, a comparative study with Egyptian and French law - Almadhaani, Mohamed Abdulla Mohamed; Hasniizam Hashim; Abdulmanan Ismail (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث تهدف هذه الدراسة الى تحليل الإطار القانوني والإجرائي للتحكيم في النزاعات الرياضية في القانون الإماراتي ومقارنته مع القوانين المصرية والفرنسية. وقد تم ذلك من خلال مقارنة بين أحكام التشريعات الرياضية في الإمارات، وتحديداً القانون الاتحادي رقم 16 لسنة 2016 الذي يتعلق بتأسيس مركز الإمارات للتحكيم الرياضي وقواعده الإجرائية، وبين أحكام قوانين الرياضة في مصر وفرنسا. وقد تم في هذه الدراسة عرض المفاهيم المتعلقة بالتحكيم الرياضي كما تم التأكيد على دور المراكز المتخصصة في التحكيم الرياضي، مثل مركز الإمارات للتحكيم الرياضي في الإمارات، والمركز المصري للتسوية والتحكيم الرياضي في مصر، وغرفة التحكيم الرياضي في فرنسا. هذا بالإضافة إلى تسليط الضوء على الإجراءات التي يجب اتباعها في عملية التحكيم الرياضي وأهمية الالتزام بها لضمان صحة وشرعية عملية التحكيم. وقد تمت مناقشة إجراءات التحكيم في المنازعات الرياضية وتحليلها بما يتوافق مع التشريعات الإماراتية والمقارنة في مصر وفرنسا. واتبع الباحث المنهج الوصفي التحليلي الاستقرائي للإطار القانوني والإجرائي للتحكيم في النزاعات الرياضية في القانون الإماراتي ومقارنته مع القانون المصري والفرنسي ليستدل منها على حقائق كاملة، وفي الختام، تبين أن المشرع الإماراتي والمشرعين المصريين والفرنسيين قاموا بتحديد إجراءات التحكيم في المنازعات التعاقدية بدءًا من تشكيل هيئات التحكيم وصولاً إلى صدور الحكم النهائي. تم التأكيد على ضرورة تحديد القوانين المطبقة على إجراءات التحكيم، سواء بالاتفاق بين الأطراف أو وفقًا للوائح الرياضية المعمول بها في الدولة. ABSTRACT This study aims to analyze the legal and procedural framework for arbitration in sports disputes in UAE law and compare it with Egyptian and French laws. This was done through a comparison between the provisions of sports legislation in the Emirates, specifically Federal Law No. 16 of 2016, which relates to the establishment of the Emirates Center for Sports Arbitration and its procedural rules, and the provisions of sports laws in Egypt and France. In this study, concepts related to sports arbitration were presented, and the role of specialized centers in sports arbitration was emphasized, such as the Emirates Sports Arbitration Center in the Emirates, the Egyptian Center for Sports Settlement and Arbitration in Egypt, and the Sports Arbitration Chamber in France. This is in addition to highlighting the procedures that must be followed in the sports arbitration process and the importance of adhering to them to ensure the validity and legitimacy of the arbitration process. Arbitration procedures in sports disputes were discussed and analyzed in accordance with UAE and comparative legislation in Egypt and France. The researcher followed the descriptive, analytical, inductive approach to the legal and procedural framework for arbitration in sports disputes in UAE law and compared it with Egyptian and French law to infer complete facts from it. In conclusion, it was found that the Emirati legislator and the Egyptian and French legislators determined arbitration procedures in contractual disputes, starting from the formation of arbitration bodies until the issuance of the final ruling. The need to determine the laws applicable to arbitration procedures was emphasized, whether by agreement between the parties or in accordance with the sports regulations in force in the country.